2010
DOI: 10.1002/app.32776
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior and mechanism of formation of protofiber morphology of solution spun poly(acrylonitrile) copolymers in DMF‐water system

Abstract: Phase diagrams of a series of copolymers of acrylonitrile (AN) and acrylic acid (AAc) were constructed using linearized cloud point correlation. The miscibility region in the phase diagram was found to increase with the increase in AAc content of the copolymers. For various compositions, v 13 (polymer-water interaction parameter) values were estimated by sorption experiment. As the hydrophilic nature of the polymer increased with the increase in the content of acrylic acid, the v 13 interaction parameter was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Furthermore, under such situation, the cross‐sectional shape of the fiber was circular, and no skin‐core morphology is visible. Many studies on the formation of macrovoids, sponge‐like, finger‐like, or macrovoid‐free structure in phase‐inversion processes can be found in the literature 19–22. The result here indicated that the coagulation condition of 60 wt % DMAc/40 wt % water was excellent for the formation of the fiber.…”
Section: Resultsmentioning
confidence: 55%
“…Furthermore, under such situation, the cross‐sectional shape of the fiber was circular, and no skin‐core morphology is visible. Many studies on the formation of macrovoids, sponge‐like, finger‐like, or macrovoid‐free structure in phase‐inversion processes can be found in the literature 19–22. The result here indicated that the coagulation condition of 60 wt % DMAc/40 wt % water was excellent for the formation of the fiber.…”
Section: Resultsmentioning
confidence: 55%
“…It is known 32 that the formation of the pores is governed by the thermodynamics and kinetics of phase F I G U R E 6 FE-SEM micrographs of the cross section of 0.2NW-FR40 fibers spun at an air gap of (A) 10 cm, (B) 2.5 cm; longitudinal section of fiber at an air gap of (C) 10 cm, (D) 2.5 cm; cross section of the fibers showing the presence of compact layer inside the fiber wall when spun at (E) 10 cm, (F) 2.5 cm and (G) Cyclic voltammogram plot of the fabricated supercapacitor device with these two fibers inversion or liquid-liquid demixing. Therefore, it was decided to change the composition of the coagulation bath to further improve the pore size distribution throughout the fiber wall.…”
Section: Resultsmentioning
confidence: 99%
“…In case of solution spinning of PAN fibres, it is well reported that the fibre morphology is highly dependent on the coagulation thermodynamics and kinetics, which ultimately determines the flexibility of the obtained fibre. In case of hollow fibres, as the bore fluid governs the coagulation of the fibre's inner surface, the use of AgNWs dispersed in pure water as the bore fluid resulted in formation of highly porous and brittle fibres.…”
Section: Resultsmentioning
confidence: 99%